STUDI KARAKTERISTIK POHON INANG ANGGREK DI KAWASAN CAGAR ALAM PANGI BINANGGA DESA SAKINA JAYA KABUPATEN PARIGI MOUTONG - Mariyanti, Rika; Mallombasang, Sri Ningsih; Ramlah, Sitti (Universitas Tadulako, 2015)
Pangi Binangga Nature Reserve is one of the conservation sites geographically located at Parigi Moutong District Central Sulawesi Province. The reserve is known to be the host of many protected species of flora and fauna including orchids. However, species richness of orchids decreased over time due to habitat degradation as well collection for commercial purposes as ornamental type of vegetation to improve community’s income. This research was to endeavor characteristics of the host trees for the orchids living in the reserve. The research was conducted from November 2014 to January 2015 using line transect methods. Transects were placed on the line purposively. Observation transects form were Quadratic with size of 20 m x 20 m. The research (applying 5 observation plots) revealed that there were 12 tree species that function as host. In general, most orchids like to have host with thick bark, coarse and scratches as well as wide canopy to cover orchids reproduction. Interestingly, it was found that each host has different orchid species (12 species). Keywords: host tree characteristics, orchids, Pangi Binangga Nature Reserve